2016
DOI: 10.1038/srep28229
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy is associated with higher risk of early recurrence and poorer survival after curative resection for early stage hepatocellular carcinoma

Abstract: Although cholecystectomy has been reported to be associated with increased risk of developing hepatocellular carcinoma (HCC), the association between cholecystectomy and prognosis of HCC patients underwent curative resection has never been examined. Through retrospective analysis of the data of 3933 patients underwent curative resection for HCC, we found that cholecystectomy was an independent prognostic factor for recurrence-free survival (RFS) of patients at early stage (BCLC stage 0/A) (p = 0.020, HR: 1.29,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
5
1
Order By: Relevance
“…A recent cohort study by Li et al demonstrated that concurrent cholecystectomy increased the risk of recurrence and negatively affected survival after surgical resection in early-stage HCC [14]. In contrast, our study indicates that cholecystectomy may reduce the risk of tumor recurrence after curative resection in patients with HCC.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…A recent cohort study by Li et al demonstrated that concurrent cholecystectomy increased the risk of recurrence and negatively affected survival after surgical resection in early-stage HCC [14]. In contrast, our study indicates that cholecystectomy may reduce the risk of tumor recurrence after curative resection in patients with HCC.…”
Section: Discussioncontrasting
confidence: 67%
“…Although a previous study reported cholecystectomy was associated with a higher risk of early recurrence and poorer survival after curative resection for early-stage HCC [14], there were still many issues unresolved. The most important was that the surgical indication of concurrent cholecystectomy in HCC patients is not widely advocated.…”
Section: Introductionmentioning
confidence: 99%
“…The BCLC stage recommended curative treatment methods for the HCC patients with single nodule or ≤3 nodules with none >3 cm, Child-Pugh classification A-B, Eastern Cooperative Oncology Group (ECOG) =0, and without gross vascular invasion and extrahepatic metastasis, which was defined as the early stage (4). The 5-year survival rate of these patients can reach 70-80% after hepatectomy (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…[3] Whether gallbladder pathologies induce hepatic disorders remains unclear. Notably, various complications can occur after cholecystectomy (ie, the symptoms of dyspepsia, bile reflux, biliary injury, and increased risks of liver fibrosis, HCC, and gastrointestinal cancer [4][5][6][7] ), implying involvement of the gallbladder in liver disorders under certain conditions.…”
Section: Introductionmentioning
confidence: 99%